ПАНЧЕНКО П.П., СЛАВОВ В.П., ШМАРЧУК В.А. Аграрна історія України. Навч.посіб. - Якименко, М. А. (Український історичний журнал, 2000)
ПАНЧЕНКО П.П., СЛАВОВ В.П., ШМАРЧУК В.А. Аграрна історія України. Навч.посіб. - К., 1996. - 405 с.